PERBEDAAN POLA MAKAN DAN STATUS GIZI SISWA ANAK SEKOLAH DASAR DARI KELUARGA NELAYAN DAN BUKAN NELAYAN DI KABUPATEN MINAHASA TENGGARA - Jufri Sineke; Mirna Kawulusan (Jurnal GIZIDO, 2015)
At this time, Indonesia faced a double nutritional problem is the problem of malnutrition and overnutrition problems. Umumya problem of malnutrition caused by poverty, lack of food supplies, lackof good kualiatas environment (sanitation), the lack of public knowledge about nutrition, abalanced diet and health and nutrition for poor areas (Iodine). Instead more nutritional problemscaused by economic progress in specific segments of society is accompanied by a lack ofknowledge about nutrition, balanced diets and health (Almatsier 2010). Nutritional problems foundin children who live on the coast and mountains. Usually the wrong diet that cause nutritionalproblems. The purpose of research to describe dietary and nutritional status of children of primaryschool students from families of fishermen and not fishermen in Southeast Minahasa Regency.This type of research is a survey research is descriptive, cross sectional study, the sampleamounted to 72 people. Data collected in the form of diet by using FFQ form and the level of foodconsumption is done with a 24-hour recall method performed 2 times. Data nutritional status ofchildren, collected using BMI index / U.The results showed that the pattern of energy consumption in general (52.7%) are less good, andonly 33.3% good, 66.7% carbohydrate consumption patterns less and 22.2% good, 58.3% proteinand 25% less good, 72.2% fat and 18.1% less well. Nutritional status of children 54.2% better, butthere is a very thin 5.5%, 22.2% and 2.7% underweight obesity. There is no difference betweenthe energy consumption patterns of children from families of fishermen with fishing instead offamily where p> 0.05, there is no difference between the pattern of nutrient consumption ofcarbohydrates with a child from a family of fishermen instead of fishing families where p> 0.05,there is no difference between the pattern of nutrient consumption of protein from fishing familieswith children instead of fishing families where p> 0.05, there is no difference between fatconsumption pattern child family fisherman with no fishing families where p> 0.05, there is nodifference between the nutritional status of children family fishermen not fishing families where p>0.05.